Against sustainability : reading nineteenth-century America in the age of climate crisis - Neely, Michelle C. (Fordham University Press, 2020)
Against Sustainability responds to contemporary environmental crisis not by seeking the origins of U.S. environmental problems, but by returning to the nineteenth-century literature and cultural contexts that gave rise to many of our most familiar environmental solutions. Chapters explore sustainability, recycling, frugality, preservation, radical pet keeping, zero waste, and utopianism.